Penerapan Regresi Nonparametrik Spline dalam Memodelkan Faktor-faktor yang Mempengaruhi Indeks Pembangunan Manusia di Provinsi Sulawesi Selatan Tahun 2015 - A. Asmira; Muhammad Nadjib Bustan; Muhammad Kasim Aidid (Universitas Negeri Makassar, 2020)
Abstrak. Human development index (HDI) is a measure used in monitoring and evaluating human development. Indicators used to measure HDI consists of three basic components of quality of life that is the life chances, knowledge and decent living standards. Several factors are thought to affect the HDI in the district/city in South Sulawesi province that labor force participation rates, the ratio of school pupils, overcrowding, health facilities, and the Gross Domestic Product (GDP). When HDI and these factors are plotted then shows the pattern of data that is not to follow a certain pattern, so that the data can be applied to the nonparametric regression model spline truncated. Selection of the best model seen from the point of knots and the minimum value of GCV. Based on research, the value of the minimum GCV is at three knots point is equal to 5.33 Rated amounting to 80.29%.Keywords: Human development Index, GCV, Nonparametric Regression Spline, Knot Points